A study on the high efficiency reduction of p-nitrophenol (4-NP) by a Fe(OH)3/Fe2O3@Au composite catalyst. Issue 43 (3rd August 2021) - Fu, Meirong; Li, Mingqiang; Zhao, Yingying; Bai, Yunxiang; Fang, Xingzhong; Kang, Xiaolong; Yang, Min; Wei, Yanping; Xu, Xia
Abstract : The process of the catalytic reduction of 4-nitrophenol based on single atom-dispersed Au loaded with ultrathin Fe(OH)3 /Fe2 O3 nanosheets. Abstract : Precious metal nanometric catalysts are widely used in the removal of harmful substances. In the process of synthesis and catalytic reaction, it is particularly important to study green and simple synthesis methods and high catalytic efficiency. In this paper, a green one-step method was used to synthesize the Fe(OH)3 /Fe2 O3 @Au composite catalyst, in which Au was single atom-dispersed. The removal of 4-nitrophenol (4-NP), a typical dangerous chemical widely existing in factory waste gas, waste water and automobile exhaust gas, was catalysed by Fe(OH)3 /Fe2 O3 @Au. The catalytic performance of Fe(OH)3 /Fe2 O3 @Au with different synthesis conditions (different amounts of MES, NaBH4, FeSO4, Au and Pt) on the 4-NP reduction reaction were systematically studied. Finally, the stability and recyclability of Fe(OH)3 /Fe2 O3 @Au composite nanocatalyst were investigated thoroughly.